2023
DOI: 10.3389/fimmu.2023.1163585
|View full text |Cite
|
Sign up to set email alerts
|

The resurgence of the Adora2b receptor as an immunotherapeutic target in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by a dense desmoplastic stroma that impedes drug delivery, reduces parenchymal blood flow, and suppresses the anti-tumor immune response. The extracellular matrix and abundance of stromal cells result in severe hypoxia within the tumor microenvironment (TME), and emerging publications evaluating PDAC tumorigenesis have shown the adenosine signaling pathway promotes an immunosuppressive TME and contributes to the overall low survival rate. Hypoxia increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…In secondary resistance, patients respond to treatment initially but develop resistance later [ 1 ] . Studies have demonstrated that the tumor mutational burden (TMB) influences the response to ICI [ 24 - 26 ] . Reduced TMB within tumors treated with ICI can result in acquired resistance to ICI immunotherapy.…”
Section: Understanding Non-responders To Immunotherapy In Solid Tumorsmentioning
confidence: 99%
“…In secondary resistance, patients respond to treatment initially but develop resistance later [ 1 ] . Studies have demonstrated that the tumor mutational burden (TMB) influences the response to ICI [ 24 - 26 ] . Reduced TMB within tumors treated with ICI can result in acquired resistance to ICI immunotherapy.…”
Section: Understanding Non-responders To Immunotherapy In Solid Tumorsmentioning
confidence: 99%
“…Additionally, A2BR plays an important role in the proliferation, differentiation, and apoptosis of cancer cells ( Guieu et al, 2021 ; Augustin et al, 2022 ). Generation of purine nucleosides in TME effectively inhibits T-cell and NK cell activities, studies have found that A2AR and A3R play critical roles in tumor immune responses ( Zahavi & Hodge, 2023 ; Strickland et al., 2023 ). Therefore, ARs have been used as therapeutic targets for novel drug development against cancers.…”
Section: Introductionmentioning
confidence: 99%